Chiral supramolecular organization and cooperativity in DNA-templated assemblies of ZnII–chromophore complexes. Issue 96 (14th November 2016) - Rubio-Magnieto, Jenifer; Kumar, Mohit; Brocorens, Patrick; Idé, Julien; George, Subi J.; Lazzaroni, Roberto; Surin, Mathieu
Abstract : Templated cooperative binding induced assembly of chromophores is achieved via interactions between Zn-complexes and the DNA phosphodiester backbone. Abstract : Templated cooperative binding induced assembly of chromophores is achieved via interactions between Zn-complexes and the DNA phosphodiester backbone. The chromophores are organized in left-handed ( M )-helices via double-zipper assembly with the DNA templates.